KONSEP MODEL STRATEGI PEMBELAJARAN PEMBIASAAN MELALUI PENDIDIKAN AGAMA ISLAM DI MADRASAH - sampara sampara; Fahrul Fahrul; Rosmila Rosmila (Prodi PAI STIT Sunan Giri Bima, 2023)
Learning the habituation method is one of the steps or ways that can be applied in preparing students to think, behave, and act. This learning model is focused on a continuous repetition process so that it can become a habit that creates a character. Following are the attitudes of habituation that need to be implemented in the learning process in the practice of Islamic religious education, namely being religious, honest, tolerant, disciplined, diligent, creative, independent, democracy, curiosity, national spirit, love of the motherland, appreciating achievement, hospitality/communication, love peace, fond of reading, interest in the environment, social, sense of responsibility. The advantages of habituation learning models such as saving energy and time besides the pattern of education touch the physical and spiritual aspects of students and are able to instill and grow the character of students. While the drawback is that this method really requires an educator who is really expected to be a role model for students.